1969
DOI: 10.1002/pssb.19690310157
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Effects in the Reflectivity Spectra of Orthorhombic Crystals Sb2S3 and Sb2Se3

Abstract: The investigation of polarization effects in the fundamental reflectivity spectra of non-cubic crystals can provide an additional information for the assignment of optical transitions (1). Related orthorhombic crystals Sb S and Sb Se are isomorphic and have layer structure, which lead to an anisotropy of electrical conductivity and edge absorption (2, 3). The energy spectrum and dipole selection rules were studied by group-theoretical methods (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 2 publications
4
13
0
Order By: Relevance
“…Comparison of this data with the results of Greenaway and Harbeke [l] on Bi,Te3-Bi,Se,, and Shutov et al [3] on the end components, Sb,Te, and Sb,Se, has shown many similarities between these systems but has raised questions concerning the chemical bonding concepts formulated to explain the properties of this class of materials.…”
Section: 'supporting
confidence: 58%
See 1 more Smart Citation
“…Comparison of this data with the results of Greenaway and Harbeke [l] on Bi,Te3-Bi,Se,, and Shutov et al [3] on the end components, Sb,Te, and Sb,Se, has shown many similarities between these systems but has raised questions concerning the chemical bonding concepts formulated to explain the properties of this class of materials.…”
Section: 'supporting
confidence: 58%
“…Thus, some differences in optical properties would be expected and are found, e.g. the smallest energy gap in Sb,Se, is a direct one, and splitting of several Sb,Se, reflectivity peaks (A4.5) occur due to lower crystal symmetry [3].…”
Section: Discussionmentioning
confidence: 99%
“…This band gap is smaller than those of binary MnS (3.2 eV) [28], and Mn 2 Sb 2 S 5 (N 2 H 4 ) 3 (2.09 eV) [21], but it is bigger than that of orthorhombic MnSb 2 S 4 (0.77 eV) [29]. In fact, the bandgap of compound 1 is comparable to that of condensed phase Sb 2 S 3 (1.7-1.9 eV) [30].…”
mentioning
confidence: 89%
“…In contrast with other members of this family, e.g., Bi 2 Se 3 , Bi 2 Te 3 , and Sb 2 Te 3 , the band structure of Sb 2 Se 3 is topologically trivial [1], hence this compound has not been in the recent focus of the condensedmatter physics community. Nonetheless, it has been widely investigated since the 1960s because of its anisotropic structure, which is responsible for intriguing anisotropic optical and transport properties [2,3]. Furthermore, this material has shown promising potential for various applications in several fields: together with other selenides and tellurides as a high-performance thermoelectric [4][5][6], as a pristine material for memory switching [7], and in its amorphous form for optical storage [8].…”
Section: Introductionmentioning
confidence: 99%